Eksistensi dan Karakteristik Putusan Bersyarat Mahkamah Konstitusi - Rahman, Faiz; Wicaksono, Dian Agung (Jurnal Konstitusi, 2016)
The result of this legal research show the existence of conditionally constitutional and conditionally unconstitutional decision in reviewing laws from 2003 to 2015, although that model of decision is not regulated in the positive law.  There are 5 characteristics of conditionally constitutional decision, those are (1)  Court  gives interpretation or certain requirements in order to remain constitutional provisions tested throughout implemented according to the specified requirements of the Constitutional Court; (2) based on the rejected verdict; (3) a conditionally constitutional clause can be found only on the consideration of the Court, or can be found on the judgment and injunction; (4) conditionally constitutional decision require re-judicial review if the norm is not in line with the interpretation of the Constitutional Court; (5) encouraging legislative review. Regarding the conditionally unconstitutional decision, there are 4 characteristics, those are (1) the verdict certainly include a conditionally unconstitutional clause; (2) a conditionally verdict can be the meaning or interpretation of a norm, or give the terms of the norm is unconstitutional; (3) based on the granted verdict either partially or completely; (4) does not substantially different from the conditionally constitutional clause.